2015
DOI: 10.1103/physrevb.91.214417
|View full text |Cite
|
Sign up to set email alerts
|

Element-specific electronic structure and magnetic properties of an epitaxialNi51.6Mn32.9Sn15.5thin film at the austenite-martensite transition

Abstract: An austenite-martensite transition was observed in a 100-nm-thick Ni 51.6 Mn 32.9 Sn 15.5 film by temperaturedependent resistivity and magnetization measurements, revealing a martensite starting temperature of M S ≈ 260 K. The influence of the structural phase transition on the electronic structure and the magnetic properties was studied element specifically employing temperature-dependent x-ray-absorption spectroscopy and x-ray magnetic circular dichroism. In addition, density functional theory calculations h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…The spinpolarized partial densities of states (DOS) of Ni 2 MnSn for the austenitic hightemperature Fm m 3 ¯ structure obtained from fully relativistic GGA calculations are presented in figure 3. The results agree well with previous band struc ture calculations [11,16,35] ) and a triplet t 2 (xy, yz, and xz). The hybridization between Ni t 2 and Mn t 2g states splits the Mn spindown t 2g states into two peaks, the bonding one located at ∼1.9 eV below the Fermi level and the unoccupied antibonding peak centered at 1.2 eV.…”
Section: Energy Band Structuresupporting
confidence: 92%
See 1 more Smart Citation
“…The spinpolarized partial densities of states (DOS) of Ni 2 MnSn for the austenitic hightemperature Fm m 3 ¯ structure obtained from fully relativistic GGA calculations are presented in figure 3. The results agree well with previous band struc ture calculations [11,16,35] ) and a triplet t 2 (xy, yz, and xz). The hybridization between Ni t 2 and Mn t 2g states splits the Mn spindown t 2g states into two peaks, the bonding one located at ∼1.9 eV below the Fermi level and the unoccupied antibonding peak centered at 1.2 eV.…”
Section: Energy Band Structuresupporting
confidence: 92%
“…In the Ni and Mnrich Ni 2+x Mn 1.4−x Sn 0.6 alloys the excess Ni atoms lead to decrease of T C , due to the dilution of the magnetic subsystems by Ni, and the increase T M , due to the increase of valence electron concentration [13]. Epitaxial thin films of Mnrich Ni-Mn-Sn alloys with a small addition of Ni over the stoichiometry were also studied in [14][15][16]. It was shown that, besides the composition, the film thickness also has significant influence on MPT.…”
Section: Introductionmentioning
confidence: 99%
“…Changing the lattice distortion from elongation to compression of the c axis is in many Heusler type compounds accompanied by a rotation of the easy axis from in-plane to outof-plane orientation. 19,47 The variation is almost linear with c/a in some cases flattening around the minima, one example is shown in Fig. 6 for Ni 2 CoGa.…”
Section: Changing the Lattice Geometrymentioning
confidence: 86%
“…Ni 2 MnGa or off-stoichiometric Ni-Mn-Z (Z = Sn, Sb, In) are well known for their shape memory behavior. 13,[18][19][20] Recently the MAE on Mn based Heusler alloys has been discussed in view of their suitability for spin transfer torque applications 12 . These systems are ferrimagnetic with a small net moment of 1-2 µ B but MAE values up to 1meV/f.u.…”
Section: Introductionmentioning
confidence: 99%
“…So far the application is handicapped by the irreversibility of the caloric response 10,[16][17][18][19] and a fundamental understanding of the magnetic phases and their impact on the metamagnetic transition is urgently needed for further optimization. The magnetic properties of Ni(Co)-Mn-(Sn,Ga,In) are far from being understood; paramagnetic, ferromagnetic, antiferromagnetic, non-collinear, spin-glass phases, FM clusters in an AF matrix, exchange bias phenomena, and reoccurrence transitions, all have been found -depend- * Electronic address: anna@thp.uni-due.de ing on temperature, composition, field treatment, and sample preparation 7,12,[14][15][16][17][19][20][21][22][23][24][25][26][27][28][29][30] . We concentrate on Ni 43.75 Co 6.25 Mn 43.75 Sn 6.25 (Ni 7 CoMn 7 Sn).…”
mentioning
confidence: 99%